PERTANIAN VERTIKAL DI ARJUNA UTARA - Christopher Darius; Lina Purnama (Jurusan Arsitektur dan Perencanaan, 2019)
Millennial are an innovative generation both in terms of technology and in solving problems. This generation has its views both on the way the world works and its impact on the environment. In terms of food availability and quality, Millennial are very concerned about their food. This generation of